2013
DOI: 10.1074/jbc.m113.487777
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Phosphate Recognition in Inositol 1,3,4,5,6-Pentakisphosphate 2-Kinase (IPK1) Substrate Binding and Activation

Abstract: Background: The mechanism of substrate recognition for IPK1 (inositol 1,3,4,5,6-pentakisphosphate 2-kinase) is unresolved.Results: Binding and activity data reveal specific roles for each phosphate of IP5.Conclusion: The phosphate profile of IP5 is mechanistically critical to IPK1 activation.Significance: Identifying determinants of substrate specificity will aid in the design of selective inhibitors for IPK1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…1), consistent with the IP-free crystal structure of IPK1 that revealed localized destabilization of the region surrounding Arg-130, which interacts with the 1-phosphate (19). We recently investigated specific roles of phosphate groups in binding and activation of IPK1, and we determined that the 5-and 6-phosphates were important for binding of the IP, whereas the 1-and 3-phosphates were important for activation of IPK1 (20). In our current study, we demonstrated that the overall stability of IPK1 is dependent on the N-lobe binding 1-and 3-phosphates (Fig.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…1), consistent with the IP-free crystal structure of IPK1 that revealed localized destabilization of the region surrounding Arg-130, which interacts with the 1-phosphate (19). We recently investigated specific roles of phosphate groups in binding and activation of IPK1, and we determined that the 5-and 6-phosphates were important for binding of the IP, whereas the 1-and 3-phosphates were important for activation of IPK1 (20). In our current study, we demonstrated that the overall stability of IPK1 is dependent on the N-lobe binding 1-and 3-phosphates (Fig.…”
Section: Discussionsupporting
confidence: 49%
“…We have also found that the 1-and 3-phosphates of the IP provide increased stability to IPK1, whereas the 5-and 6-phosphates do not affect the overall stability of IPK1, consistent with an unstable N-lobe and a stable C-lobe in the absence of IP. Moreover, previous kinetic studies of IPK1 link substrate specificity to kinase activation (20). We contend that IPK1 stability is linked to IPK1 activation because IPK1 stability correlates with the active state in previous crystal structures (19), IPs that display low IPK1 kinase activity (k cat ) correlate with a decreased ability to stabilize IPK1 (20), and kinase stability has been validated to be a precursor for activation of PKs, for which IPK1 shares similar features (9,15).…”
Section: Ip-induced Stabilization As a Model Of Ip Recognition For Ipk1-mentioning
confidence: 99%
See 3 more Smart Citations